A modelagem matemática e o desenvolvimento da autonomia : um estudo com estudantes do ensino médio - Galvani, Ingridi Rodrigues Charal (2016)
This research aims to identify attitudes of students in the development of Mathematical Modeling activities that are concerned with the autonomy characteristics according to Paulo Freire. To support this research used as a methodology to action-research, for the support in the analysis of the actions developed in the classroom, along with a characterization of autonomy according to Paulo Freire's books: Pedagogy of Autonomy: knowledge necessary for educational practice, For a Pedagogy of Question and Pedagogy of the Oppressed, that during the Modeling activity enable the development of the autonomy of the student. Data collection was carried out in a class of 3rd year of High School, the public school system, the nighttime, located in a town northwest of Paraná, during classroom observation and the implementation of three Mathematics Modeling activities. The analysis of the interventions during the of Mathematical Modeling activities proposed activities show that students' attitudes, own the modeling activity favor the development of their autonomy